Development and the African diaspora place and the politics of home - Mercer, Claire (London Zed Books, 2008)
This innovative book examines the relationship between African "civil society" and "home association" networks in the diaspora. Remittances home via these networks outweigh official development assistance. Looking in particular at Cameroon and Tanzania, the authors argue that building "civil society" in Africa must be understood in tandem with the political economy of migration and wider debates concerning ethnicity and belonging. They demonstrate both that diasporic development is distinct from mainstream development, and that it is an uneven historical process in which some '"homes" are better placed to take advantage of global connections than others. In doing so, the book engages critically with the current enthusiasm among policy-makers for treating the African diaspora as an untapped resource for combating poverty.
Includes bibliographical references (p. [236]-251) and index.
Keywords: African diaspora -Economic aspects